Busca de serviços baseada em perfis sociais de objetos em redes SIoT - Araújo, Iury Rogério Sales de (2019)
The rapid growth in the number of Internet-connected devices has had a major impact on the Internet of Things (IoT) infrastructure. This creates several challenges for service and object management, such as scalability, heterogeneity, and the massive data transferred. A new paradigm, called Social Internet of Things (SIoT), has been proposed to address the challenges facing IoT, introducing the concept of social networking to organize and manage objects, thus providing improvements to the network functionalities. As a new paradigm, SIoT presents challenges to adapte functionalities from the IoT middleware, as the service discovery, to a new social context. Another challenge is to integrate the potential offered by social networks into the middleware features, like the abstraction of objects through their characteristics and information, which can be represented by the social profiles. Such profiles offer the ability to create and use relationships between objects to assist in the management of services, like the discovery.This research proposes a service discovery method based on the characteristics and information of objects contained in their social profiles to assist the service management in IoT networks. Tests performed showed the effectiveness of the proposed discovery method in finding objects that meet the requests more satisfactorily when compared to those in the literature.